HAK TANGGUNGAN ATAS HAK GUNA BANGUNAN DI ATAS TANAH HAK MILIK - I Wayan Suka Antara Yasa; I Made Suwitra; I Nyoman Alit Puspadma (Jurnal Hukum Prasada, 2017)
Abstract Based on Government Regulation No. 40 of 1996 concerning the rights of cultivation, the rights of building and the rights of use, it's known about the granting of the building rights on the land of ownership rights, use a deed of issued by the PPAT. But in practice at the city of Denpasar, preceded by deed of agreement and deed of authority of issued by Notary Public. In this case, the problems arise of the how about the legal certainty, the legal enforceability, the legal protection and the usefulness of the law. And then how about the legal protection to the ownership holder when the building rights used as collateral of mortgage rights. The research was conducted empirically with the statute approach, case and analytic approach. Data are obtained from primary and secondary data with documentary studies and interviews. And then, the data analitical uses a qualitative analysis. Based on the results of the study, conclusions obtained the deed of agreement and the deed of authority in a granting of a building rights on the land of ownership rights in the city of Denpasar has fulfilled the aspects of legal certainty, to be effective in the people community for the benefit and legal protection both for ownership rights holders and building rights holders. Besides that, the study also conclude that the ownership holders lack of preventive legal protection, but it, at the refresif legal protection, the ownership rights holders have been protected legally if the building rights on the land of his ownership rights burdened with mortgage rights. Keyword : Ownership Rights, Building Rights, Mortgage Rights